The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1148/radiol.13121351
|View full text |Cite|
|
Sign up to set email alerts
|

Automated Detection of Sclerotic Metastases in the Thoracolumbar Spine at CT

Abstract: Purpose:To design and validate a computer system for automated detection and quantitative characterization of sclerotic metastases of the thoracolumbar spine on computed tomography (CT) images. Materials and Methods:This retrospective study was approved by the institutional review board and was HIPAA compliant; informed consent was waived. The data set consisted of CT examinations in 49 patients (14 female, 35 male patients; mean age, 57.0 years; range, 12-77 years), demonstrating a total of 532 sclerotic lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 40 publications
0
60
0
Order By: Relevance
“…It can be seen that the classification performance saturates quickly with increasing N . This means the run-time efficiency of our second Figure 7 compares the FROCs from the initial (first layer) CADe system [9] and illustrates the progression towards the proposed coarse-to-fine two tiered method in both training and testing datasets. This clearly demonstrates a marked improvement in performance.…”
Section: Evaluation and Results On Sclerotic Metastasesmentioning
confidence: 94%
“…It can be seen that the classification performance saturates quickly with increasing N . This means the run-time efficiency of our second Figure 7 compares the FROCs from the initial (first layer) CADe system [9] and illustrates the progression towards the proposed coarse-to-fine two tiered method in both training and testing datasets. This clearly demonstrates a marked improvement in performance.…”
Section: Evaluation and Results On Sclerotic Metastasesmentioning
confidence: 94%
“…Additionally, compared to prior CT-based detection systems designed for sclerotic lesion detection, 9,13,14 lytic lesion detection, 6,7 and sclerotic/lytic but not mixed type detection, 15,16 this system uses a triple classifier process to detect all three lesion types: lytic, sclerotic, and mixed. Additionally, compared to Ref.…”
Section: Discussionmentioning
confidence: 99%
“…The group later applied the technique to detect changes in lytic metastases from one cohort of patients taking bisphosphonates and one control cohort. 11 For sclerotic lesion CAD, Weise et al 12 and Burns et al 13 developed a sclerotic metastasis detection system on CT and examined the etiology of false negative and false positive detections. Roth et al 14 then proposed a deep convolutional neural network approach to reduce the number of false positives in the sclerotic metastasis CAD.…”
Section: Introductionmentioning
confidence: 99%
“…challenging tasks of automatic detection and recognition of anatomical structures and pathological lesions in cross-sectional imaging remain part of intensive research. Burns et al recently demonstrated an automated algorithm for detection of bone metastasis [19]. Several prior studies have investigated techniques for automated labeling and segmentation of the spine [16][17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…To cope with the resulting large volume of data, an increasing number of software tools support the radiologist's work in routine clinical practice and accelerate the work processes, examples are lesion detection and tracking in oncology [16][17][18][19]. Nevertheless, challenging tasks like automatic detection and correct anatomical labeling of vertebral bodies are part of current research [16,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%